Tax avoidance and management fraud in malaysian public limited companies: conceptual paper / Roshidah Safeei - Safeei, Roshidah (Universiti Teknologi MARA, Kedah, 2022)
Tax avoidance and management fraud have occurred all over the world every year. This study aims to examine the association between tax avoidance and the incidence of alleged management fraud in Malaysia. Hence, this study attempts to investigate the influence of tax avoidance on management fraud in public companies listed in the Main Market of Bursa Malaysia. This study used secondary data and quantitative analysis. The unit of analysis of this study was companies being prosecuted by the Securities Commission of Malaysia for management fraud from 2017 to 2020. Apart from contributing to the tax avoidance and management fraud literature, this study is expected to benefit various parties especially regulators and policymakers such as the Inland Revenue Board of Malaysia, Bursa Malaysia and Securities Commission of Malaysia to improve the tax system and financial reporting quality in Malaysia. This study enhances public understanding of tax avoidance and management fraud as well as well as contributes to improve detection, deterrence, and investigation of tax avoidance and management fraud.